2021
DOI: 10.1177/18479804211056162
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hollow and spherical cadmium sulphide nanoparticles by an unconventional design of bioelectrochemical system

Abstract: The synthesis of CdS nanoparticles was developed based on the unconventional design of bioelectrochemical system (BES) inoculated with Shewanella sp. HN-41. The BES configuration included two bottle chambers separated by silicon membrane but directly connected by a graphite electrode perforating through silicon membrane, namely, non-external circuit bioelectrochemical system (nec_BES). Shewanella sp. HN-41 in the anode of nec_BES consumed lactate and transferred electrons to the graphite electrode end in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Previous studies with bioelectrochemical systems (BESs) showed that Cu ions were removed from a cathodic solution to produce pure and aggregated Cu or CuO particles. 16,17 Therefore, in this study, we applied a new design of BES, 18,19 which is composed of two chambers (anode and cathode) connected by a graphite rod to evaluate the possibility and chemical structure of synthesized Cu nanoparticles and also the antibacterial activities of the produced nanoparticles. The produced particles were characterized by SEM, TEM, and XRD, and tested for their antimicrobial activities against plant pathogens ( X. axonopodis and R. solanacearum ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with bioelectrochemical systems (BESs) showed that Cu ions were removed from a cathodic solution to produce pure and aggregated Cu or CuO particles. 16,17 Therefore, in this study, we applied a new design of BES, 18,19 which is composed of two chambers (anode and cathode) connected by a graphite rod to evaluate the possibility and chemical structure of synthesized Cu nanoparticles and also the antibacterial activities of the produced nanoparticles. The produced particles were characterized by SEM, TEM, and XRD, and tested for their antimicrobial activities against plant pathogens ( X. axonopodis and R. solanacearum ).…”
Section: Introductionmentioning
confidence: 99%